John Chapman papers - Chapman, John, 1801-1854.
Correspondence, writings, notes, and patent specifications relating to aerial steam navigation and to the aerodynamic and propeller theories of William S. Henson. Includes drafts of articles and diagrams by Chapman and Henson.
John Chapman, British editor and political journalist; and William S. Henson, British aerodynamics engineer and inventor.
Collection material in English.
Keywords: Aerodynamics; Aeronautics -- Great Britain; Propellers, aerial; Steam-navigation.; Henson, William S. -- 1805?-1888.; Editors -- Great Britain; Journalists